El registro de mayor altitud del Hurón Mayor Galictis vittata, con notas sobre su presencia y conservación dentro del departamento de Caldas, en la región andina de Colombia - Escobar-Lasso, Sergio; Guzmán-Hernández, Cristian F. (THERYA, 2014)
Introduction: The Greater Grison Galictis vittata is distributed in the northern part of Latin America, from southern Mexico through Central America to reach northern Bolivia and Brazil, from sea level to 1.500 m, being more common below 500 m. In the department of Caldas, located in the Central Cordillera of Colombia, there is no literature to collect information of G. vittata. Therefore, the aim of this paper is to present the record of greater height of the species, conduct a review of the distribution of G. vittata within the Caldas department, and investigate about threats to their populations in that region. Materials and methods: To carry out the review of the distribution and conservation of G. vittata within the Caldas department, were taken into account: A) Specimens, or part of these, deposited within biological collections. B) Records in scientific literature. C) Photographic records. D) Records of live individuals coming from the Caldas department who entered to the Center of Care, Assessment and Rehabilitation of Wildlife of the Regional Autonomous Corporation of Caldas (Corpocaldas). Results and discussion: To date, there are records in the municipalities of Manizales, Marquetalia, and Villamaría, between 900 and 2,200 m. In this work, we determined that this was the highest elevation that has been reported to date for this species not only in Colombia but throughout all its range of distribution. Its main threats within the Caldas department are illegal hunting and habitat loss. In the department of Caldas, the majority of the records are concentrated on the banks of the Guarino River, in the municipality of Marquetalia. We proposed that the area of the Guarino River, could be protected to prevent the local extinction of G. vittata in that department.